Częstość danych statystycznych a wyniki prognozowania - Hamulczuk, Mariusz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2003)
The purpose of this article is to find relations between forecast results and data frequency used as an example. The example concerns monthly, quarterly and half-yearly sugar prices from London Stock, 1994-2001. The Brown's linear and quadratic as well as Holt's exponential smoothing methods were employed to made the prediction. Obtained results indicate the influence of frequency data on forecasting results.lw